Performance Measurement System Design, Competitive Capability, and Performance Consequences - A Conceptual Like - Ibrahim Ali, Abushaiba; Yuserrie, Zainuddin (Centre for Promoting Ideas, USA, 2012)
The recently days business environment requires management accounting information to provide relevant measures of performance, and reflect the strategic goals of a modern firms. The performance measurement system (PMS) developed as strategic orientation aimed at providing information to enhance the firm’s strategic goals. It is interesting to introduce the PMS design which is externally and future oriented to overcome the weakness of traditional PMS and for strategic outcomes. Apparent gaps seem to be attributed to its various conceptualizations resulted from fragmented efforts on the development PMS. Furthermore, inherited by the scarcity of empirical studies, evidence had been exploratory and little is known about PMS design and its effects on strategic outcomes. The impact of PMS design on the performance is sparse significantly. In terms of essential characterization PMS, that might help to explain how the system has beneficial direct effects on firm's outcomes and indirect through the firm’s competitiveness. Thus, based on in-depth review on existing literature on the PMS, this paper develops a proposed theoretical framework. Specifically, the objectives of this paper are three folds; Firstly, it attempts to unravel the various perspectives and define PMS design and suggest on how it might be further developed. Secondly, employing contingency theory as its underpinning theory this paper posits firm’s competitiveness as Intervening variable to explain the relationship. Finally, its possible performance are put forth to legitimize the development as an important remedial to the traditional performance measurement system in aiding firm's long –term survival.